Pengaruh Financial Performance Terhadap Financial Distress Pada Perusahaan Subsektor Customer Non Cyclical - Apriliantika, Annisa; Agung Praptapa (Universitas Islam Negeri K.H. Abdurrahman Wahid Pekalongan, 2025)
Financial distress occurs when a company faces ongoing operational losses that lead to a shortage of capital. The conditions of financial distress can be identified and assessed through the analysis of financial statements. Various factors, including financial performance, can influence financial distress. This research seeks to investigate the impact of return on assets, cash ratio, and debt-to-equity ratio on financial distress. The research employs a quantitative method using secondary data, with purposive sampling to select eight non-cyclical consumer companies listed on the IDX from 2019 to 2023. The analysis is conducted using multiple regression analysis via SPSS version 25. The findings reveal that return on assets negatively impacts financial distress; higher profits tend to attract investor interest, thereby reducing the likelihood of financial difficulties. Conversely, the cash ratio does not significantly affect financial distress, indicating that both high and low cash ratio values do not necessarily correlate with the risk of financial problems. Similarly, the debt-to-equity ratio also shows no effect on financial distress, suggesting that investors' decisions to invest are not swayed by changes in the debt-to-equity ratio as reflected in financial statements.